A class of evolutionary models for participation games - Pietro Dindo; Jan Tuinstra (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
We introduce a framework to analyze the interaction of boundedly rational heterogeneous agents repeatedly playing a participation game with negative feedback. We assume that agents use different behavioral rules prescribing how to play the game conditionally on the outcome of previous rounds. We update the fraction of the population using each rule by means of a general class of evolutionary dynamics based on imitation, which contains both replicator and logit dynamics. Our model is analyzed by a combination of formal analysis and numerical simulations and is able to replicate results from the experimental and computational literature on these types of games. In particular, irrespective of the specific evolutionary dynamics and of the exact behavioral rules used, the dynamics of the aggregate participation rate is consistent with the symmetric mixed strategy Nash equilibrium, whereas individual behavior clearly departs from it. Moreover, as the number of players or speed of adjustment increase the evolutionary dynamics typically becomes unstable and leads to endogenous fluctuations around the steady state. These fluctuations are robust with respect to behavioral rules that try to exploit them.
Keywords: C72; C73; 330; Participation games; Heterogeneous behavioral rules; Revision protocol; Replicator Dynamics; Logit Dynamics; Nonlinear dynamics; Spieltheorie; Evolutionsökonomik; Verhalten; Logit-Modell; Nichtlineare dynamische Systeme; Simulation